Al-Shaykh Muḥammad Zain Shukrī: Imtidād al-Turāth al-Fikrī li ‘Ulamā’ Fālimbānj fī al-Qarn al-‘Ishrīn al-Mīlādī - Zulkifli Zulkifli (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2002)
This present article, which was written to try to fill the gap, discusses a figure, namely K.H.M. Zen Syukri, who was one of the productive and influential religious scholars in Palembang at the beginning of the 20th century. Issues such as his biography and religious thoughts, his activities and roles in the spheres of education, dakwah (missionary) and in that of socio-politics are discussed. But more specifically, the article is concerned with the role of K.H.M. Zen Syukri in the development of the Sammaniyyah Order in South Sumatera.DOI: 10.15408/sdi.v9i1.677